Sistem Informasi Penyedia Lowongan Kerja Dinas Tenaga Kerja dan Transmigrasi Kabupaten Lombok Tengah - Leni Sefvia; Mohammad Taufan Asri Zaen; Khairul Imtihan (Journal of Informatics Management and Information Technology, 2022)
In finding job vacancy informations, job seekers still use the manual method by visiting companies, looking at job vacancies bulletin boards, doing a search in print media, this makes it difficult for job seekers to find job vacancies informations so that the unemployment rate in the Central Lombok region is getting higher. The research aims to build an informations system that provides informations on vacancies being managed by the Department of Manpower and Transmigration that may make it easier for job seekers to find the oppropriate Before building an informations system, researchers have collected data by means of observation, interviews, and for system design using the Waterfall method. The results obtained by testing the system using Black-Box , all the features in the system are running well. Meanwhile, user satisfaction testing using the WebQual 4.0 method obtained results of 86,76% to 91,24% which showed users strongly agree that this job vacancy informations system can be operated easily